(untitled) (Studi di storia medioevale e di diplomatica - Nuova Serie, 2020)
The paper analyzes some case studies related to the territory of the city and the diocese of Novara. They are intended as examples within a general survey aimed at showing the economic impact and the effective yield of the income from the noble class. The research started from the episcopal lordship of Vespolate begun in the thirteenth century. Later, through complex events, the lordship was acquired by the Visconti, who attributed it on several occasions to people linked to them, such as Stefano and Antonio Porro, or Francesco Barbavara. The different types of income received by the Archbishop of Milan between 1379 and 1382, concerning thirty Vergante settlement centers, were also evaluated. This territory, strategically important and of primary importance from the commercial point of view, was granted in feud during the XV century to the Borromeo for intervention of the Milanese dukes, continously in search of financing and cash subsidies. The increase of rural and territorial lordships through feudal concessions clearly comes out from the analysis of the case of Vinzaglio, while among the examples useful to deepen the concessions of lordships to men of arms, stands out Briona, entrusted to Giovanni Tornielli. Finally, the cases of Galliate, Intra, Pallanza and Cameri are proposed, to show the attempts made by the communities to free them from feudal submission.